PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING DENGAN PENDEKATAN STEM TERHADAP HASIL BELAJAR SISWA SMA - Teguh Wijayanto; Bambang Supriadi; Lailatul Nuraini (JURNAL PEMBELAJARAN FISIKA, 2020)
The learning model project based learning is an instructional model that can be applied to the STEM approach. Approach STEM (Science, Technology in, Engineering and Mathematic) is an approach that can be used in learning by using multiple disciplines. STEM approach in learning is very suitable to be applied in the curriculum in 2013 so that students are able to be more active, creative, and better understand the concepts taught in a material for a project which produced students in learning directly related to real-life experience of students in the everyday. The purpose of this study was to determine the influence of the learning model project based learning with STEM approach to the learning outcomes of high school students. The research was conducted in class X IPA 1 SMA Muhammadiyah 3 Jember, with 32 students at 15 male students and 17 female students. The method used in this research is the method pre-experiment design with one group pretest-posttest design. Collecting data in this study using the initial test and final test. Student learning outcomes obtained after application project based learning model STEM learning approach shows N-gain category was at 0.62. Keywords: project based learning, approach STEM, learning outcomes.